KEBIASAAN MEROKOK, PENGGUNAAN APD, DAN GANGGUAN PERNAPASAN PEKERJA GUDANG SEMEN TIGA RODA BENGKULU - Utami, Sulthanah (JURNAL MEDIA KESEHATAN, 2017)
Respiratory disorders are human lung function damage due to blockage of therespiratory tract by dust respiratory disorders. The research problem is the high smokingand lack of PPE in cement warehouse workers. The purpose of research known relationshipof smoking habits and personal protective equipment (PPE) with respiratory distresson three wheels cement warehouse worker Bengkulu. Type a descriptive study usingcross sectional approach. Subjects consisted of 35 respondents. Data were collected byquestionnaire directly to the job site. Univariate and bivariate analysis with Chi-squaretest. The results of data analysis showed that the value of ρ = 0.001 (ρ ˂ 0,005) smoking(81.0%) there is a link cigarette smoking with breathing disorders, the value ρ = 0.011 (ρ˃ 0,005) did not wear PPE (72%) there is no relationship APD with respiratory disorders.Suggested workers using PPE in the form of a mask while working or while in the surroundingarea cement storage warehouse. The company also advised medical check up onworkers to control the physical condition of workers so that the worker is known to havesuffered respiratory problems.